117 Quantitative CT Ventriculography for Assessment and Monitoring of Hydrocephalus: A Pilot Study and Description of Method in Subarachnoid Hemorrhage. (August 2016) - Oermann, Eric Karl; Multani, Jasjit; Mascitelli, Justin Robert; Skovrlj, Branko; Pain, Margaret; Nicole, Kelly; Titano, Joseph; Costa, Anthony; Shrivastava, Raj K.
Abstract : INTRODUCTION: There is no quantitative method for monitoring hydrocephalus. We propose a method whereby computer image analysis combined with computed tomographic (CT) scanning can achieve this in a clinical subarachnoid hemorrhage (SAH) setting. METHODS: Twenty patients with SAH underwent formal clamp trials and evaluation for shunting and were selected for inclusion. Patients with intraventricular hemorrhage were excluded. Ten patients with normal head CT scans were analyzed as negative controls. CT scans were obtained per standard protocol with average (Z, Y, X) voxel dimensions of (51, 512, 512). Images were segmented both manually and semiautomatically (quantitative CT [qCT], ventriculography) to generate measures of ventricular volume. RESULTS: Average manually calculated ventricular volume was 61.5 cm 3 (SEM 15.9 cm 3 ) equivalent to an average qCT ventriculography volume of 61.0 cm 3 (SEM 15.6) ( P = .796). Clamp trials lasted, on average, 3 days for the patients who did not undergo shunting, and 4 days for the patients who eventually were shunted. Patients undergoing shunting demonstrated an increase in ventricular volume on qCT ventriculography from 21 to 40 cm 3 on day T-2, and 51 cm 3 by day 0, a change of 144%. This contrasts with patients who did not require shunting whose ventricular volumes decreased from 16 to 14 cm 3 on day T-2, and 13 cm 3 by the end, with an average overall decrease in volume of 19% ( P = .001). Average change in ventricular volume predicted which patients would require shunting, successfully identifying 7/10 patients ( P = .004). Using an optimized cutoff of change in ventricular volume of 2.5 cm 3 identified all patients who went on to require shunting (10/10, P = .011). CONCLUSION: qCT ventriculography is a reliable means of quantifying ventricular volume and hydrocephalus. This technique offers a new tool for monitoring neurosurgical patients in both the inpatient and outpatient setting for hydrocephalus, and may be beneficial for use in future research clinical trials as well as the routine care of patients with hydrocephalus.